Switzerland : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Selected Issues paper and Statistical Appendix compares two alternative time series approaches to analyzing Switzerland's recent business cycle experience: first, the traditional 'smooth-trend-plus-cycle approach,' which envisages observed output growth as fluctuating around a relatively smooth potential output growth path; and, second, the more recently developed 'regime change approach,' which views business cycles as shifts between 'high-growth' states (expansions) and 'slow-growth' states (recessions) of the economy. The paper also examines Switzerland's monetary policy framework, and describes the challenges to the Swiss tax system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet